Coronary Artery Fistula Unmasking the Absence of Left Pulmonary Artery in an Adult - Sigusch, Holger H.; Hansch, Andreas; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Coronary artery fistulae are an incidental finding in patients undergoing coronary angiography or computed tomography (CT) coronary angiography. A 60-year-old man with known coronary artery disease presented with dyspnea. Coronary angiography revealed a large fistula arising from the circumflex artery (CX) without a clear intrathoracic target vessel or chamber in the heart. CT angiography revealed the agenesis of the left pulmonary artery. The fistula arising from the CX ensured left lung tissue supply. Unilateral absence of a pulmonary artery is an extremely rare condition. In this case, the identification of a fistula from the heart triggered the correct diagnosis.
Keywords: congenital defect; myocardial infarction; pulmonary arteries